Caracterização de sementes de uma variedade crioula de milho pipoca (Zea mays L. subsp. mays) cultivada em sistema orgânico - Cheim, Loanda Maria Gomes (2021)
Popcorn is a popular preparation, easy to prepare and affordable price. Due to this and the interest and demand of consumers for foods with higher nutritional quality, there is an increase in their cultivation and consumption worldwide. Landrace popcorn (LP) are cultivated in family farming. The objective of this study was to identify the race and characterize LP in an organic system by family farmers in terms of its physical characteristics, physiological properties, nutritional value, bioactive compounds content, and antioxidant activity (AA). LP was analysed for the phenotypic characterization and race identification, germination and vigor, thickness/width ratio, circularity index, sphericity, diameter ratio, geometric mean diameter, volume, surface area, angle of repose (AR), hectoliter weight (HW), apparent specific gravity (ASG), thousand kernel weight (TKW), color, and classification according to identity and quality requirements, determined the contents of moisture, carbohydrate, protein, lipid, ash, total dietary fiber (soluble and insoluble), minerals, monomeric anthocyanins, total phenolic compounds (TPC), AA (DPPH, FRAP and ABTS), and carotenoid profiles. LP is of an indigenous Guarani origin and belongs to the Avatí Pichingá Ihú race. The variety yields a high germination and vigor and can be used as seeds. The dimensions and calculated indices had important variations among the grains, demonstrating a wide genetic diversity, typical of landraces. The low AR, associated with the dimensions, revealed the small size of the LP grains. Higher values for HW, ASG, and TKW indicated higher levels of vitreous endosperm, hardness, and starch content. The coordinates a * and b * respectively indicate the red and yellow colors while the low value for the parameter L * indicates the intense color of the LP. Corn was classified as type 1 according to the percentage of physical defects, however, the expansion capacity presented a value below the reference for commercialization. LP, classified in this work as PAPI (Avatí Pichingá Ihú popcorn) presented contents of proteins, fibers, P, K, S, Cu, and TPC in levels higher than those found in the literature. In addition to evidence of the presence of other phytochemicals, different from anthocyanins and carotenoids, verified by the content of TPC and AA observed in the reduction capacity of ABTS, FRAP, and DPPH radicals. The moderate lipid content in PAPI allows its consumption by patients with dyslipidemia and liver disease. These characteristics associated with the high content of insoluble fibers, which exerts satiety effects, the lower carbohydrate and calorie content, when compared to other samples, without the addition of oil, butter, and sugar in its preparation, allows PAPI integrate a healthy diet, without promoting weight gain. The potential of the studied variety is verified to be used by industries, mainly the food sector. Its cultivation can be stimulated by family farming, ultimately impacting grain production and promoting the rescue of germplasm.